THE RECOGNITION AND RIGHTS PROTECTION FOR BATIN SEMBILAN COMMUNITIES OVER CUSTOMARY TERRITORY AND NATURAL RESOURCE MANAGEMENT - Manik, Herlina; Suhermi, Suhermi; Sasmiar, Sasmiar; Herlina, Nelli (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2023)
Conflicts over land tenure and other sources of natural resources have been persistent for a long time and have led to a process of structural poverty; the loss of local wisdom in managing natural resources; and even the elimination of communities from their living space. Although there are many policies that contain recognition of indigenous peoples’ rights, recognition of rights to customary territories has never existed and evictions of the Batin Sembilan community still continue. The specific objectives that researchers want to achieve in this research are to examine and analyze the existence of Batin Sembilan community; and analyze the mechanism of recognition and protection of the community there in managing natural resources. This research combines qualitative research through primary data collection from the field, making observations, while also using secondary data, especially related to government policies, regulations and programs to provide a general understanding of the real conditions faced by the Batin Sembilan community. Based on the results of this research, it is expected to generate findings regarding the mechanism for recognizing and protecting the rights of Batin Sembilan people to customary territories and natural resource management.